Enhancing Educational Quality Through Facilities and Infrastructure Management: Evidence from an Islamic Primary School - Indah Komsiyah (Al-Qalam Institue, 2026)
This study aims to analyze the implementation of facilities and infrastructure management in improving the quality of education at an Islamic elementary school. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, passive participant observation, and documentation involving the principal, facilities and infrastructure coordinator, finance officer, and teachers selected through purposive sampling. Data were analyzed using an interactive model consisting of data collection, condensation, data display, and conclusion drawing. The credibility of the findings was ensured through source and technique triangulation. The findings reveal that facilities and infrastructure management is implemented through participatory planning aligned with curricular needs, priority-based procurement according to budget availability, systematic asset inventory and administration, and collaborative utilization and maintenance involving all school members. These practices contribute to creating a conducive learning environment, enhancing teaching effectiveness, and supporting improvements in educational quality. The study implies that systematic and participatory management of educational facilities and infrastructure is essential for strengthening institutional quality and sustaining educational excellence in Islamic primary schools.